Komparasi Konsep An-Nafs dalam Al-Qur’an dan Teori Sigmund Freud - Urgenadila, Aulia; Soleh, Achmad Khudori (MOMENTUM : Jurnal Sosial dan Keagamaan, 2023)
An-Nafs in the Qur’an and Sigmund Freud’s theory both have three components in the soul. An-Nafs Al-Ammarah with Id, An-Nafs Al-Lawwamah with Ego, and An-Nafs Al-Muthma’innah with Superego. In the Al-Qur’an itself Nafs is mentioned as many as 295. 140 verses that mention nafs, in the plural form nufus there are 2 verses. And in other forms of jama’ anfus there are 153 verses. The purpose of this paper are (1) to know the concept of each An-Nafs in the Qur’an and the theoretical concept of the father of psychoanalysis, namely Sigmund Freud. (2) Knowing the comparison between the two concepts, both Nafs in theology in the Qur’an and Sigmund Freud's Id, Ego, Superego. The method used is a Literature Study. The results of this study indicate that there is a comparison between the concept of An-Nafs in the Qur'an and Sigmund Freud's theoretical concept. Especially in the concept of An-Nafs Al-Ammarah with Id. Then An-Nafs Al-Lawwamah with Ego. And An-Nafs Al-Muthma’innah with Superego.